Scaling a Software Business The Digitalization Journey - Fitzgerald, Brian; Stol, Klaas-Jan; Minör, Sten; Cosmo, Henrik (Springer International Publishing : Imprint: Springer, 2017)
This book is open access under a CC BY 4.0 license.  Software has changed the rules of the game. The world talks about the digitalization in industry and society - how the focus has shifted from producing tangible things towards software and services. This trend started many years ago, but is now affecting every company, whether it's a software company or not. There are many companies that have already made a digitalization journey - and many are about to embark on this journey - like you. How do you transform your organization when software is becoming a critical part of your business? This book presents the Scaling Management Framework, a model based on collected experiences from companies that have already made the journey to give software a central role within the organization. The model is unique because it suggests a holistic method to analyze and plan your journey. It simply means that you can't just focus solely on your products or services. You also have to look closely at your processes and your organization, the way you make decisions and get things done. Inevitably, these will have to change. This book comes with a map, a compass, and suggested journeys along with selected travel stories comprising best practices and lessons learned from past digitalization journeys. Use the map to find your way in the digitalization landscape, and use the compass to find the direction of your journey.